Evolution of power China's struggle, survival, and success - Li, Xiaobing; Tian, Xiansheng (Lexington Books, 2014)
This wide-ranging, provocative, and multi-disciplinary collection of essays by U.S.-based Chinese scholars discusses most of the core problems facing China, a rising power, whose domestic and international trajectory is of vital importance to all concerned observers.